IDENTIFIKASI PERUBAHAN POLA CURAH HUJAN MELALUI PERIODOGRAM STANDAR - Gumgum Darmawan; Budhi Handoko; Zulhanif Zulhanif (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2017)
Rainfall is time series data that has seasonal pattern, usually period 12. The pattern of rainfall seasonal itself often changes. In this paper, the pattern of rainfall will identify by Periodogram Analysis. We use Time series data from one of city in west Java province. By this analysis, it is proved that the pattern of rainfall has been change. Computation itself, we use macro of Open Source Software R (OSSR).